Epidemiological Characteristics of Acute Leukemia in Child Welfare Hospital in Baghdad - Samahir A. Fadel (Journal of Global Pharma Technology, 2020)
Background: Acute leukemia, the most common form of cancer in children, comprises approximately 30% of all children malignancies, with acute lymphocytic leukemia (ALL) being more common than Acute Myeloid Leukemia (AML) by five times. Objectives: To determine different epidemiological variables associated with acute leukemia& to determine the patterns according to socio demographic data. Patients and Methods: A cross- sectional study and the data collection was carried out for a period of four months, from the 2nd /May/2019 to 2nd /September /2019. Result: The study shows that the majority of patients were ALL & the highest percentage of ALL patients was in the age group (5-9) years, males showed higher percentage than females in both type of leukemia, the highest percentage were from Urban.The majority of patient’s parents’ education level was primary; while the highest percentage of fathers’ occupation was Private sectors & the highest percentage of mothers’ occupation were Housewife.The highest percentage of ALL patients were 4th & more Order in family& AML were the 1st child, the highest percentage of patients with Birth space (2-4) years from there brothers.The highest percentage of patients was feed from their mothers (Breast feeding) during their first year & the highest percentage of patients was normal birth weight.Majority of patient’s Parent consanguinity were not related, while the lowest percentage of patient’s Parent consanguinity were far related.There was an important association between  patients’ blood group AB & ALL. Conclusions: The study shows that the majority of patients were ALL & the highest percentage of ALL patients was in the age group (5-9) years, males showed higher percentage than females in both type of leukemia, the highest percentage were from Urban. Recommendations: Ensure good MCH system to monitor and ensure the quality of health care practice & demonstrating cultural competency to promoting more effective child health services.Keywords: Leukemia, Blood, Cancer, Childhood, Iraq.